2014
DOI: 10.18632/oncotarget.1765
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in IDH1, IDH2, and in the TERT promoter define clinically distinct subgroups of adult malignant gliomas

Abstract: Frequent mutations in isocitrate dehydrogenase 1 and 2 (IDH1 and IDH2) and the promoter of telomerase reverse transcriptase (TERT) represent two significant discoveries in glioma genomics. Understanding the degree to which these two mutations co-occur or occur exclusively of one another in glioma subtypes presents a unique opportunity to guide glioma classification and prognosis. We analyzed the relationship between overall survival (OS) and the presence of IDH1/2 and TERT promoter mutations in a panel of 473 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
179
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 235 publications
(204 citation statements)
references
References 34 publications
20
179
2
Order By: Relevance
“…On the other end of the glial tumor spectrum, primary glioblastoma has been delineated as a distinct entity of highly malignant tumors characterized by the absence of IDH1/2 mutation, gains on chromosome 7 and losses on chromosome arm 9p and chromosome 10, frequent mutations in the phosphatase and tensin homolog on chromosome 10 (PTEN) gene and the human telomerase (TERT) promoter, as well as activation of receptor tyrosine kinase pathways, in particular the epidermal growth factor receptor (EGFR) and platelet-derived growth factor receptor pathways [17,25].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other end of the glial tumor spectrum, primary glioblastoma has been delineated as a distinct entity of highly malignant tumors characterized by the absence of IDH1/2 mutation, gains on chromosome 7 and losses on chromosome arm 9p and chromosome 10, frequent mutations in the phosphatase and tensin homolog on chromosome 10 (PTEN) gene and the human telomerase (TERT) promoter, as well as activation of receptor tyrosine kinase pathways, in particular the epidermal growth factor receptor (EGFR) and platelet-derived growth factor receptor pathways [17,25].…”
Section: Introductionmentioning
confidence: 99%
“…Current molecular marker-based approaches explore the validity of a three-tiered approach delineating (i) IDH1/2-mutant tumors with 1p/19q co-deletion which often carry mutations in the Drosophila homolog of capicua (CIC) gene as well as the TERT promoter and predominantly include oligodendroglial tumors, (ii) IDH1/2 mutant tumors without 1p/19q co-deletion which often carry tumor protein p53 (TP53) as well as ATP-dependent X-linked helicase (ATRX) gene mutations and predominantly include astrocytic tumors, and (iii) IDH1/2 wild-type tumors that remain poorly characterized in terms of other molecular alterations [15,17,38]. In addition, recent data from exome sequencing of anaplastic astrocytomas suggested a distinct mutation profile from primary glioblastomas, including frequent mutations in Notch pathway genes [18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the survival analysis, previous studies demonstrated the prognostic significance of IDH1 mutations (Arita et al., 2015; Brennan et al., 2013; Ducray et al., 2011; Hartmann et al., 2010; Killela et al., 2014; Lewandowska et al., 2014; Mellai et al., 2011; Olar et al., 2012; Parsons et al., 2008; Polivka et al., 2014; Sanson et al., 2009; Shibahara et al., 2011; Sun et al., 2013; Takano et al., 2012; Weller et al., 2009). Some authors observed that OS and PFS in IDH mutated cases were about twice longer than in wild‐type patients (Arita et al., 2015; Polivka et al., 2014), and others showed that mutation in IDH1 was an independent factor for a favorable prognosis (Brennan et al., 2013; Ducray et al., 2011; Polivka et al., 2014; Sanson et al., 2009; Shibahara et al., 2011).…”
Section: Discussionmentioning
confidence: 99%